A 19 year follow‐up of a woman with lipoprotein lipase deficiency treated with biliopancreatic diversion. Issue 12 (5th November 2015) - Nosso, Gabriella; Capaldo, Brunella; Cocozza, Sara; Vaccaro, Olga
Key Clinical Message: We show the long‐term efficacy and safety of modified biliopancreatic diversion for the treatment of LPL‐deficiency. How this option compares with gene therapy is difficult to evaluate due to limited experience. Surgery may be the first option in patients in whom medical therapy is ineffective and gene therapy not applicable. Abstract : We show the long‐term efficacy and safety of modified biliopancreatic diversion for the treatment of LPL‐deficiency. How this option compares with gene therapy is difficult to evaluate due to limited experience. Surgery may be the first option in patients in whom medical therapy is ineffective and gene therapy not applicable.